PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Hendri Jopanda (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2021)
The research was conducted at PT. Pasifik Satelit Nusantara research aims to determine the effect of leadership style and work environment on employee performance through job satisfaction as an intervening variable. The sample in this study amounted to 100 samples with the technique of determining the number of samples used. This type of research is a quantitative analysis (statistics). With the help of SPSS 22 software, the results show that Leadership Style has no direct effect on Job Satisfaction, Work Environment has a direct effect on Job Satisfaction, Leadership Style has no direct effect on Employee Performance, Work Environment has a direct effect on Employee Performance, Job Satisfaction has a direct effect on Employee Performance , Leadership Style has an indirect effect on Employee Performance through Job Satisfaction and the Work Environment has a direct influence on Employee Performance through Job Satisfaction.